PRMT5 Inhibitor Synergizes with Chemotherapy to Induce Resembling Mismatch Repair Deficiency and Enhance Anti‐TIGIT Therapy in Microsatellite‐Stable Colorectal Cancer - Jiang Zhu; Shenao Fu; Xi Zou; Hanjiang Zeng; Guangzu Cui; Yinghui Peng; Diya Tang; Fan Zhang; Hong Shen; Shan Zeng; Ying Han (Advanced Science)
Abstract Microsatellite stable (MSS) colorectal cancer (CRC) is considered an “immune‐cold” tumor, accounting for ≈85% of all CRC cases. The overall response rate to chemotherapy combined with immune checkpoint inhibitors in MSS CRC is typically less than 10%. The specific mechanism that enhances chemotherapy sensitivity and mediated immunogenicity renders MSS CRC more responsive to immunotherapy remains elusive. Experiments in this study identify a DNA damage repair‐related epigenetic gene, protein arginine methyltransferase 5 (PRMT5), whose inhibition enhances Irinotecan (CPT‐11) sensitivity and synergistically induces a postmeiotic segregation increased 2 (PMS2)‐deficient‐like state, leading to the release of cytosolic double‐stranded DNA. This activates the cyclic GMP‐AMP synthase (cGAS)‐stimulator of the IFN gene (STING) signaling pathway, thereby enhancing anti‐tumor immunotherapy through dendritic cell‐T cell‐dependent functions. Importantly, combining the epigenetic anti‐tumor drug GSK3326595 with CPT‐11 significantly upregulates the immune receptor tyrosine‐based inhibitory motif (TIGIT) level on CD8+ T cells and subsequently demonstrates impressive anti‐tumor efficacy in vivo when additional anti‐TIGIT is included. Collectively, this study reveals the crucial role of PRMT5 blockade combined with CPT‐11 in inducing a mismatch repair deficiency‐like state and provides a novel triple‐drug combination therapy strategy as a potential treatment for patients with MSS CRC.